Att möta skogsägare i ett urbaniserat samhälle - Andersson, Johan (2017)
The purpose with this study in forest management is to analyze the problem of forest owners’ needs of forestry services in an urbanized society. This study has also been conducted to investigate how the foresters should act to meet the different requirements when times change. The keywords are urbanization, forest owners’ in an urbanized society and forestry services. The report is the result of a collaboration between the forest owners’ association Södra Skogsägarna and the student. It is a big challenge for the forester to meet forest owners’ in an urbanized society. Nearly 60 percent of the forest owners’ in the study believes that there will be more distant owned forests in the future. It means that there will be an increasing need of an improved digital communication, requirement of knowledge and availability in the next generation forest owners’. For the forest owners’ associations, it is important to follow the trend of development.